(untitled) (Faridpur Medical College Journal, 2011)
The Lateral medullary syndrome is not a very common stroke. Sometimes it is under diagnosed. Mr. Ibrahim Mollah, 50 years old male person, non diabetic, non hypertensive but smoker presented with the history of sudden onset of dysphagia, dysarthria and ataxia of the gait. He is clinically and radiologically diagnosed as a case of Lateral medullary syndrome (Ischaemic stroke). With treatment this patient improved significantly. It is commonly caused by occlusion of the cranial segment of the vertebral artery or the posterior inferior cerebellar artery. The occlusion may be due to thrombosis or embolism. The emboli are coming from the heart or the great vessels. We can diagnose Lateral medullary syndrome with expert clinical eye and CT/MRI of the brain. It should be managed with appropriate treatment and physiotherapy. DOI: 10.3329/fmcj.v5i1.6813 Faridpur Med. Coll. J. 2010;5(1):35-36